Efektifitas Program PPA-PKH di Kabupaten Ponorogo: Tinjauan Yuridis Sosiologis - Ridho Rokamah (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2015)
The PPA-PKH program has been implemented in Ponorogo District, specifically PPA-PKH which was implemented in 2011 - 2013, and has had many positive impacts on the reduction of child labor. The target of the PPA-PKH program is to return children who work and drop out of school back to school. However, an initial survey found that some participants of the PPA-PKH program were still reluctant to return to school and chose to continue working. Therefore, the researcher is interested in further examining how the effectiveness of the implementation of this PPA-PKH program with the formulation; 1) how is the effectiveness of the implementation of data verification and validation of the PPA-PKH program in Ponorogo Regency, 2) how is the effectiveness of the implementation of the program for 1 month in the shelter of the Ponorogo Regency Vocational Training Center (BLK), and 3) how is the effectiveness of post-shelter coaching in fulfilling the basic rights of child workers who participate in the PPA-PKH program in Ponorogo Regency? The results of this study are: First, the verification and validation of data carried out by the PPA-PKH program implementers in Ponorogo Regency has been effective after following the procedures of the central PPA-PKH implementers. Second, the implementation of the PPA-PKH program for one month in the shelter is effective and in accordance with the provisions of the PPA-PKH program from the center, Third, the post-shelter coaching conducted by the PPA-PKH program implementation committee of Ponorogo Regency cannot be effective because 1) the implementation time is too short, 2) the school distance is too long from the implementation time, 3) the post-shelter coaching budget is inadequate, and 4) the paradigms of participants and people are difficult to change in a short time.